The impact of an energy-induced EU recession on Sub-Saharan Africa - Dirk Kohnert (Zenodo, 2022)
The EU is one of the three largest economies in the world. But its economy, which is still suffering from the cCOVID-19 pandemic and the negative effects of the Russian war in Ukraine, faces a bleak outlook. Inflation, or even stagflation, is a major concern as it reflects cost pressures from disrupted supply chains and tight labor markets. The war in Ukraine could also lead to a sustained stop in European gas supplies from Russia. Fitch Ratings therefore forecast the likelihood of a technical recession in the euro zone due to ongoing gas rationing. Apparently the EU is at the mercy of two unpredictable powers, Putin and the weather. China is also affected by global imbalances, and when China coughs, Europe catches the flu. However, the risks are greatest in sub-Saharan Africa. Its global growth spillovers come mainly from the EU and the BRICS countries. In addition to its strong demographic growth, the continent is already suffering from climate change, including prolonged droughts, and political destabilization, particularly in the Sahel, Horn of Africa and East Africa. The two major African powers, Nigeria and South Africa, are currently going through major socioeconomic crises. Many sub-Saharan African countries are heavily dependent on energy and food imports, particularly wheat from Russia and Ukraine. For the approximately 30 million African poor, this means an increase in inequality. A recession in Europe would amplify external pressures and growth challenges. In addition, the emerging sub-Saharan markets bear the greatest export risk to the EU. The debt problem is also looming again, because lower global commodity prices slowed down economic growth – – Die EU gehört zu den drei größten Volkswirtschaften der Welt. Doch ihre Wirtschaft, die immer noch unter der Corona-Pandemie und den negativen Auswirkungen des russischen Krieges in der Ukraine leidet, sieht sich düsteren Aussichten gegenüber. Inflation oder sogar Stagflation geben Anlass zu großer Sorge, da sie den Kostendruck durch unterbrochene Lieferketten und angespannte Arbeitsmärkte widerspiegeln. Der Krieg in der Ukraine könnte zudem zu einem anhaltenden Stopp der europäischen Gaslieferungen aus Russland führen. Fitch Ratings prognostizierte daher eine technischen Rezession in der Eurozone aufgrund der anhaltenden Gasrationierung. Offenbar ist die EU der Gnade zweier schwer einzuschätzender Mächte ausgesetzt, Putin und dem Wetter. Auch China ist von globalen Ungleichgewichten betroffen, und wenn China hustet, bekommt Europa die Grippe. In Subsahara-Afrika sind die Risiken jedoch am größten. Seine globalen Wachstums-Spillover-Effekte kommen hauptsächlich aus der EU und den BRICS-Staaten. Neben seinem starken demografischen Wachstum leidet der Kontinent bereits unter dem Klimawandel, einschließlich anhaltender Dürren, sowie politischer Destabilisierung, insbesondere in der Sahelzone, am Horn von Afrika und in Ostafrika. Die beiden afrikanischen Großmächte, Nigeria und Südafrika, durchleben derzeit große sozioökonomische Krisen. Viele afrikanische Länder südlich der Sahara sind stark abhängig von Energie- und Lebensmittelimporten, insbesondere von Weizen aus Russland und der Ukraine. Für die rund 30 Millionen afrikanischen Armen bedeutet dies eine Verschärfung der Ungleichheit. Eine Rezession in Europa würde externe Belastungen und Wachstumsherausforderungen verstärken. Darüber hinaus tragen die aufstrebenden Subsahara-Märkte das größte Exportrisiko in die EU. Auch die Schuldenproblematik droht erneut, denn niedrigere globale Rohstoffpreise bremsten das Wirtschaftswachstum.
Keywords: D31; D62; E24; F13; I31; N17; O15; P26; 330; EU; recession; Russo-Ukrainian War; COVID-19 pandemic in Africa; Sub-Saharan Africa; economic development; poverty; famine